THE UNITED NATIONS AS BEACON OF WORLD PEACE AND CONTRIBUTION OF BANGLADESH IN PEACEKEEPING - Chowdhury, Mesbah Uddin (Bangladesh Journal of Multidisciplinary Scientific Research, 2022)
The United Nations (UN) came into being in 1945 to restore peace and dignity worldwide following the devastation of the Second World War. Within a very short period, the UN gained trust for its extraordinary contributions to recuperating peace and prosperity. The UN is considered a herald of peace due to peacekeeping missions (UNPKOs). So far, more than 3,500 peacekeepers from 120 countries have sacrificed their lives to eradicate violence and animosity since 1948. As of late, Bangladesh has regained the top position among troop senders in UNPKOs, which made Bangladesh the largest contributor. Now, Bangladesh has a rich history of UNPKOs participating in 54 missions. Currently, 6,692 personnel are working on 11 missions in 5 different countries. By participating and gaining first-hand experiences, Bangladesh would easily overcome the shortcoming and make the best possible use of opportunities lying ahead. This paper attempts to depict that there is no substitute for reconstructing a violence-free world. Now more than ever, Bangladesh could be a diligent fighter on this path, keeping hand in hand with the United Nations. JEL Classification Codes: D74, P16.